Adsorption of Hg2+ by thiol functionalized hollow mesoporous silica microspheres with magnetic cores1. Issue 63 (10th July 2015) - Zhang, Xian; Wu, Tianxing; Zhang, Yunxia; Ng, Dickon H. L.; Zhao, Huijun; Wang, Guozhong
<x xml:space="preserve">Abstract</x> Thiol functionalized hollow mesoporous silica spheres with magnetic cores were synthesized and found to be highly selective adsorbents of Hg2+.